2011
DOI: 10.1371/journal.pone.0021491
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Receptor Mediated Transduction of Dendritic Cells by Lentiviruses Enveloped with Glycoproteins Derived from Semliki Forest Virus

Abstract: Lentiviruses have recently attracted considerable interest for their potential as a genetic modification tool for dendritic cells (DCs). In this study, we explore the ability of lentiviruses enveloped with alphaviral envelope glycoproteins derived from Semliki Forest virus (SFV) to mediate transduction of DCs. We found that SFV glycoprotein (SFV-G)-pseudotyped lentiviruses use C-type lectins (DC-SIGN and L-SIGN) as attachment factors for transduction of DCs. Importantly, SFV-G pseudotypes appear to have enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Crosslinking of DC-SIGN at the cell surface by multiple high-mannose sites on the virion triggers uptake of the bound particle, resulting in antigen capture (see [29] for a recent review). DC-SIGN is used by many viruses for attachment to DCs, including MV [30], HIV-1 (see the recent review in [31]), HCV [32][33][34], Influenza A viruses [35,36], the herpes simplex virus type 1 [37], the human cytomegalovirus [38], Ebola virus [39], the SARS coronavirus [40,41], the human T-cell leukemia virus type 1 [42,43], and arboviruses belonging to the flavivirus genus -dengue virus [44,45] and west nile virus [46]) -and to the alphavirus genus, like SV [47] and aura virus [48]. In this review, we focus on recent insights for understanding the mechanism by which DC-SIGN signaling induces the uptake of the virus particle by the cell, beyond the initial attachment step.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinking of DC-SIGN at the cell surface by multiple high-mannose sites on the virion triggers uptake of the bound particle, resulting in antigen capture (see [29] for a recent review). DC-SIGN is used by many viruses for attachment to DCs, including MV [30], HIV-1 (see the recent review in [31]), HCV [32][33][34], Influenza A viruses [35,36], the herpes simplex virus type 1 [37], the human cytomegalovirus [38], Ebola virus [39], the SARS coronavirus [40,41], the human T-cell leukemia virus type 1 [42,43], and arboviruses belonging to the flavivirus genus -dengue virus [44,45] and west nile virus [46]) -and to the alphavirus genus, like SV [47] and aura virus [48]. In this review, we focus on recent insights for understanding the mechanism by which DC-SIGN signaling induces the uptake of the virus particle by the cell, beyond the initial attachment step.…”
Section: Introductionmentioning
confidence: 99%
“…At 24 h, Johnson et al observed an increase in Langerhans cell density upon intradermal injection of wild-type SFV [ 41 ]. Despite the limited capacity of SFV to infect DCs in vitro , strategies have focused on targeting dendritic cells with the use of lentiviruses enveloped with glycoproteins derived from SFV by attaching to C-type lectins [ 42 ]. Langerhans cells may also shuttle virus particles by attachment to DC-SIGN, as observed in the case of HIV infection [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these data, we demonstrated that DC-SIGN plays a role in the high-level transduction of MDDCs by H/F-LVs. Interestingly, DC-SIGN appears to be targeted by multiple native viruses (36), and it was used as a major DC specific target receptor for redirecting LV vector tropism both in vitro and in vivo, i.e., mainly dermal DCs (31,32,63,89). In addition, DC-SIGN has been shown to mediate suppression of innate immune responses via the TLR-dependent expression of the regulatory cytokine IL-10 by DCs (44,45).…”
Section: Discussionmentioning
confidence: 99%